Heterozygous mutations in HSD17B4 cause juvenile peroxisomal D-bifunctional protein deficiency. (December 2016) - Amor, David J.; Marsh, Ashley P.L.; Storey, Elsdon; Tankard, Rick; Gillies, Greta; Delatycki, Martin B.; Pope, Kate; Bromhead, Catherine; Leventer, Richard J.; Bahlo, Melanie; Lockhart, Paul J.
Abstract : Objective: To determine the genetic cause of slowly progressive cerebellar ataxia, sensorineural deafness, and hypergonadotropic hypogonadism in 5 patients from 3 different families. Methods: The patients comprised 2 sib pairs and 1 sporadic patient. Clinical assessment included history, physical examination, and brain MRI. Linkage analysis was performed separately on the 2 sets of sib pairs using single nucleotide polymorphism microarrays, followed by analysis of the intersection of the regions. Exome sequencing was performed on 1 affected patient with variant filtering and prioritization undertaken using these intersected regions. Results: Using a combination of sequencing technologies, we identified compound heterozygous mutations in HSD17B4 in all 5 affected patients. In all 3 families, peroxisomal D-bifunctional protein (DBP) deficiency was caused by compound heterozygosity for 1 nonsense/deletion mutation and 1 missense mutation. Conclusions: We describe 5 patients with juvenile DBP deficiency from 3 different families, bringing the total number of reported patients to 14, from 8 families. This report broadens and consolidates the phenotype associated with juvenile DBP deficiency.